Perencanaan Kewirausahaan Berbasis Digital Melalui Kanalyoutube Musik Jazz Herdito Tamami - Moch Herdito Tamami (JEMAP, 2020)
The fast echnology development from time to time, gives indirect impact in business environment which brings change in market environment. Herdito Tamami Youtube is created as media to acknowledge Jazz Music to Semarang society and its surroundings. Innovation was conducted to Herdito Tamami Youtube by market expanding, increasing competitive advantage, and getting new income source. Feasibility study toward business innovation through youtube canal is conducted to know how far this innovation gives impact to Herdito Tamami Youtube. This Classroom Action Research method used mixed method. Primary data was get by interview and direct observation toward Jazz lovers and performers and email interview to Indonesian youtuber. From the research result, it is found that business innovation of Herdito Tamami Youtube through youtube canal can expand market reach, increase competitive advantage in theme originilatity and its topic, but not yet give new income source outside main activity. From feasibility study of innovation, it was found that this innovation was worth to be developed and increased concerning its future income.